Peran Literasi Digital dalam Meningkatkan Partisipasi Masyarakat di Era Transformasi Digital - Jolanda Tomasouw; Juliaans E. R. Marantika; Ronald Darlly Hukubun; Chlaudia Novita Ilery; Bryan Latarissa; Aldea Duingga; Aldrian Salamor (Faedah: Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
Digital literacy is an essential competency in the era of digital transformation because it involves not only technical skills but also the ability to critically understand information in cyberspace. A good level of digital literacy can encourage community participation in public decision-making and democratic processes, while inequality in access and digital literacy skills may hinder such participation. Therefore, this community service activity aims to improve digital literacy in order to overcome challenges and strengthen inclusive community participation. The activity targeted children and adolescents in Waihoka Village, Ambon City, with 31 participants involved in socialization Alexistoto and educational sessions. Evaluations were conducted before and after the presentation of the material, and the results showed an increase in participants’ understanding of digital literacy from early childhood to adolescence. Thus, communities with adequate digital literacy are expected to be more capable of accessing information, interacting appropriately in digital spaces, and actively participating in public decision-making processes and social activities in the digital era.